Pharmacological impact of Agaricus bisporus extract in carbon tetrachloride-induced hepatotoxicity in rats - Rizk, Manar; El-Deberky, Deena; El-Sayed, Faten; Amin, Aziza; El-Mahmoudy, Abubakr (International Journal of Pharmacology and Toxicology, 2020)
Drug-induced hepatotoxicity is a frequent cause of liver injury worldwide. The present study was designed to evaluate the possible hepato-protective potential Agaricus bisporus extract (ABE; a type of mushrooms) in albino rats using Carbon tetrachloride (CCl4)-model of liver injury. Forty-two albino rats were utilized in this experiment arranged randomly in seven groups, six rats each, of different treatments. He-patic injury model was induced by administration of CCl4 (25% in corn oil) at a dose of 2.5 ml/kg, interperitoneally, twice weekly for 8 weeks (+ve control); test group rats received ABE at escalating doses of 200 or 400 mg/kg, orally, daily for 8 weeks with exposure to CCl4; standard group rats received Silymarin at dose of 100 mg/kg, orally, daily for 8 weeks along with CCl4; further 2 groups of rats received only ABE at the same dose levels; while rats of -ve control group received only the vehicles of the used drugs. Blood and liver tissue sam-ples were picked out at the end of the experimental course for different assays. Biochemical analysis revealed that ABE exhibited dose-dependent hepatoprotection indicated by almost normalized biomarkers, including, enzymatic liver function parameters, namely, AST, ALT, GGT & ALP with potential % of 93.1, 58.2, 65.2, 68.9, respectively, after ABE large dose when standardized by Silymarin; non-enzymatic parameters, namely, total protein, albumin, globulins, total bilirubin, conjugated bilirubin, unconjugated bilirubin, TAGs, Cholesterol, HDL, LDL & VLDL with potential % of 59.3, 54.5, 57.3, 81.8, 81.0, 80.0, 75.5, 90.4, 80.8, 84.5 & 78.7, respectively, after ABE large dose when standardized by Silymarin. The mechanism of the obtained hepatoprotection of ABE may be based on impeding the oxidative stress mediated by the used hepatotoxin, indicated by reduced MDA (37.9 % of Silymarin), and restored SOD, Catalase & GPx in liver homogenate with potentials of 94.9, 63.0 & 88.4 % of Silymarin, respectively. Pathological findings, both macroscopic and microscopic, were supportive to the biochemical findings, where the pathological lesions caused by CCl4 as fatty degeneration of hepatocytes with vacuolated cytoplasm, proliferated fibrous connective tissue with eosinophilic edematous fluid cells plus focal and diffuse necrotic areas and hyperplastic biliary epithelium, were ameliorated dose-dependently when ABE was administered together with CCl4. Data of the present study may suggest ABE as a good natural source for promising hepatoprotective and antioxidative remedies.